A PBT composite material, its preparation method and application

By adding an appropriate amount of halogen absorber and talc powder to the PBT composite material, the problem of insufficient heat resistance performance of flame retardant-enhanced PBT materials at long-term high temperatures is solved, and the long-term heat resistance and yellowing resistance of the material are significantly improved.

CN116606533BActive Publication Date: 2025-04-01KINGFA SCI & TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310662385.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-06
Publication Date
2025-04-01
Estimated Expiration
2043-06-06

AI Technical Summary

Technical Problem

When used at long-term high temperatures, existing flame retardant reinforced PBT materials have insufficient heat resistance, which affects their service life.

Method used

By adding an appropriate amount of halogen absorber and talc powder to the PBT composite material, and limiting its particle size range and mass ratio, an excellent compounding effect is formed, effectively absorbing free bromine generated by bromine flame retardant during the aging process, thereby improving the thermal oxygen aging performance of the material.

Benefits of technology

It significantly improves the long-term heat resistance and yellowing resistance of PBT composite materials, while maintaining its flame retardant and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004269584090000051
    Figure BDA0004269584090000051
  • Figure BDA0004269584090000052
    Figure BDA0004269584090000052
  • Figure BDA0004269584090000061
    Figure BDA0004269584090000061
Patent Text Reader

Abstract

The invention discloses a PBT composite material and a preparation method and application thereof, belonging to the technical field of polymer engineering plastics; the PBT composite material provided by the invention comprises the following components in parts by mass: 40-60 parts of PBT resin, 25-40 parts of glass fiber, 8-20 parts of brominated flame retardant, 1-5 parts of flame retardant synergist, 0.3-1.1 parts of halogen absorbent, and 0.5-2 parts of talcum powder; the average particle size of the talcum powder is 0.6-5 μm; the mass ratio of the halogen absorbent to the talcum powder is 1:(1-5), and the halogen absorbent is hydrotalcite or zeolite. The PBT composite material provided by the invention has excellent heat resistance, wherein the tensile property retention rate of the obtained product after aging in an oven at 190°C for 1000h is above 67%; and the preparation method provided by the invention is simple, which is conducive to actual production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer engineering plastics, and in particular relates to a PBT composite material and a preparation method and application thereof. Background Art

[0002] Flame retardant reinforced PBT is widely used in the fields of electronic appliances, fans, lighting, and home appliances due to its excellent mechanical properties, electrical properties, and heat resistance. At present, the vast majority of PBT products are flame retardant reinforced PBT, among which 30% glass fiber is the most widely used. In actual use, whether in the fields of lighting, fans, home appliances, or electronic appliances, PBT works at a relatively high temperature, which poses a challenge to the heat resistance of the product, especially the long-term heat resistance, which is the most critical factor affecting its service life.

[0003] Regarding improving the long-term heat resistance of flame-retardant reinforced PBT, the current main research idea is to optimize the antioxidant system. Literature reports that the glass fiber reinforced PBT material with a ternary antioxidant system of hindered phenol antioxidants, organic sulfur antioxidants and carbon radical scavengers has the best comprehensive performance against thermal oxidative aging, which can improve the mechanical property retention rate and yellowing resistance of the material during long-term thermal oxidative aging. However, according to our research results, antioxidants have a significant effect on the short-term processing thermal stability of flame-retardant reinforced PBT, but have no significant effect on the long-term thermal oxidative aging performance. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a PBT composite material which can maintain basic mechanical properties and flame retardant properties while also having excellent long-term heat resistance, and a preparation method and application thereof.

[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a PBT composite material, which includes the following components in parts by mass: 40-60 parts of PBT resin, 25-40 parts of glass fiber, 8-20 parts of brominated flame retardant, 1-5 parts of flame retardant synergist, 0.3-1.1 parts of halogen absorbent, and 0.5-2 parts of talcum powder; the average particle size of the talcum powder is 0.6-5μm; the mass ratio of the halogen absorbent to the talcum powder is 1:(1-5), and the halogen absorbent is hydrotalcite or zeolite.

[0006] In a PBT composite material provided by the present invention, a halogen absorber and talcum powder are added in appropriate mass parts and mass ratios, and the average particle size range of the added talcum powder and the specific selection of the halogen absorber are limited, so that the two can play an excellent compounding effect, effectively absorbing the free bromine generated by the bromine flame retardant during the aging process, and then significantly improving the effect of the thermal oxygen aging performance of the composite material, and will not cause losses to the flame retardant properties and mechanics of the composite material; the compounding of the specific halogen absorber and talcum powder selected at the same time can also significantly improve the yellowing resistance of the composite material. The present invention defines that the halogen absorber is specifically hydrotalcite or zeolite, wherein hydrotalcite (LDHs) has a layered structure, and the layer plate of LDHs is composed of magnesium octahedron and aluminum oxygen octahedron, has strong alkalinity, and has a strong adsorption capacity for free bromide ions; zeolite is generally a hydrous alkali metal or alkaline earth metal aluminosilicate mineral, has a porous structure, a high specific surface area, and has ion exchangeability, so it can better adsorb free bromide ions.

[0007] As a preferred embodiment of the PBT composite material of the present invention, the mass ratio of the halogen absorbent to talc is 1:(2-3).

[0008] When the mass ratio of the halogen absorber to talcum powder is further optimized to be 1:(2-3), the tensile property retention rate of the obtained product after aging in an oven at 190°C for 1000 hours is higher, at more than 72%, and the yellowing resistance is also better.

[0009] As a preferred embodiment of the PBT composite material of the present invention, the average particle size of the halogen absorbent is 0.1-10 μm.

[0010] The inventors have found that when the average particle size of the halogen absorbent is further limited to 0.1-10 μm, the halogen absorbent can be compounded with talcum powder to produce a better effect, thereby making the product's heat-oxidative aging resistance and yellowing resistance better.

[0011] As a preferred embodiment of the PBT composite material of the present invention, the brominated flame retardant is at least one of brominated epoxy, brominated polystyrene, brominated polycarbonate, decabromodiphenylethane, pentabromobenzyl polyacrylate, and bromotriazine.

[0012] As a preferred embodiment of the PBT composite material of the present invention, the flame retardant synergist is an antimony-containing flame retardant.

[0013] Preferably, the flame retardant synergist is antimony white or sodium antimonate; more preferably, the flame retardant synergist is antimony white or sodium antimonate to ensure excellent flame retardant properties of the product.

[0014] As a preferred embodiment of the PBT composite material of the present invention, the PBT composite material further comprises the following components in parts by weight: 0.01-5 parts of a toughening agent and 0.01-1 parts of a processing aid.

[0015] As a preferred embodiment of the PBT composite material of the present invention, at least one of the following (a)-(d) is included:

[0016] (a) the intrinsic viscosity of the PBT resin is 0.7-1.3 dL / g at 25° C. (for example, the intrinsic viscosity of the PBT resin at 25° C. may be 0.70 dL / g, 0.71 dL / g, 0.72 dL / g, 0.73 dL / g, 0.74 dL / g, 0.75 dL / g, 0.76 dL / g, 0.77 dL / g, 0.78 dL / g, 0.79 dL / g, 0.80 dL / g, 0.81 dL / g, 0.82 dL / g, 0.83 dL / g, 0.84 dL / g, 0.85 dL / g, 0.86 dL / g, 0.87 dL / g, 0.88 dL / g, 0.89 dL / g, 0.90 dL / g, 0.91 dL / g, 0.92 dL / g, 0.93 dL / g, 0.94 dL / g, 0.95 dL / g, 0.96 dL / g, 0.97 dL / g, 0.98 dL / g, 0.99 dL / g, 0.91 L / g, 0.81dL / g, 0.82dL / g, 0.83dL / g, 0.84dL / g, 0.85dL / g, 0.86dL / g, 0.87dL / g, 0.88dL / g, 0.89dL / g, 0.90dL / g, 0.91dL / g, 0.92dL / g, 0.93dL / g, 0.94dL / g, 0.95dL / g, 0.96dL / g, 0.97 dL / g, 0.98dL / g, 0.99dL / g, 1.00dL / g, 1.01dL / g, 1.02dL / g, 1.03dL / g, 1.04dL / g, 1.05dL / g , 1.06dL / g, 1.07dL / g, 1.08dL / g, 1.09dL / g, 1.10dL / g, 1.11dL / g, 1.12dL / g, 1.13dL / g, 1.1 4dL / g, 1.15dL / g, 1.16dL / g, 1.17dL / g, 1.18dL / g, 1.19dL / g, 1.20dL / g, 1.21dL / g, 1.22dL / g, 1.23dL / g, 1.24dL / g, 1.25dL / g, 1.26dL / g, 1.27dL / g, 1.28dL / g, 1.29dL / g, 1.30dL / g, etc.);

[0017] (b) the glass fiber is an alkali-free glass fiber treated with a coupling agent;

[0018] (c) the toughening agent is at least one of ethylene-acrylate-glycidyl methacrylate terpolymer, ethylene-acrylate binary copolymer, ethylene-vinyl acetate, and glycidyl methacrylate grafted ethylene-octene copolymer;

[0019] (d) The processing aid is at least one of a lubricant and an antioxidant.

[0020] Selecting the PBT resin with the above intrinsic viscosity can be beneficial to the stability of the injection molding process.

[0021] The intrinsic viscosity of the PBT resin is tested according to GB / T 14190-2017.

[0022] The present invention has no special requirements for glass fiber, and is preferably alkali-free glass fiber treated with a coupling agent, and the diameter is preferably 8-15μm, such as 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, and 15μm can all achieve the present invention; the coupling agent used is a silane coupling agent.

[0023] Preferably, the lubricant is at least one of aliphatic carboxylic acid esters, erucamide, ethylene bisstearamide, montan esters, polyethylene wax, and oxidized polyethylene wax; and the antioxidant is at least one of hindered phenol antioxidants, phosphite antioxidants, and organic sulfur antioxidants.

[0024] In addition, the present invention also provides a method for preparing the PBT composite material, which comprises the following steps: weighing the dried raw materials, mixing them and feeding them into a twin-screw extruder, extruding, drawing, cooling, pelletizing and drying to obtain a polyester composite material.

[0025] As a preferred embodiment of the preparation method of the present invention, the drying process of the PBT resin is: drying the PBT resin at 120-140° C. for 4-6 hours.

[0026] As a preferred embodiment of the preparation method of the present invention, the parameters of the twin-screw extruder are: a feeding rate of 450-800 kg / hour; the temperatures of each section of the screw from the feeding port to the die are 220-230°C, 230-240°C, 230-240°C, 240-250°C, 250-260°C, 240-250°C, 240-250°C, 230-240°C, and 220-230°C respectively; and the screw speed is 250-400rpm.

[0027] In addition, the present invention also provides the application of the PBT composite material in the field of household appliances and electronic appliances. For example, the PBT / PC composite material is used in the manufacture of integrated circuits, capacitors, switches, relays, connectors, transformer skeletons, cables, cooling fans, and low-voltage electrical appliances.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention provides a PBT composite material, wherein a halogen absorber and talcum powder are added in appropriate parts by mass and in a mass ratio, and the average particle size range of the added talcum powder and the specific selection of the halogen absorber are limited, so that the two can achieve an excellent compounding effect, effectively absorb the free bromine generated by the bromine-based flame retardant during the aging process, and then significantly improve the thermal oxygen aging performance of the composite material, and will not cause losses to the flame retardant performance and mechanics of the composite material; at the same time, the halogen absorber and talcum powder selected to be added can also significantly improve the yellowing resistance of the composite material; wherein the obtained product has an initial tensile strength of more than 120MPa, a tensile performance retention rate of more than 67% after aging in an oven at 190°C for 1000h, and a yellowing resistance value of less than 13ΔE; and the preparation method provided by the present invention is simple and is conducive to actual production. DETAILED DESCRIPTION

[0030] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0031] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0032] PBT resin 1: intrinsic viscosity 0.8dL / g, PBT 1200-211M, Changchun, Taiwan, China;

[0033] PBT resin 2: intrinsic viscosity 1.31dL / g, PBT GL236, Yizheng Chemical Fiber, China;

[0034] Brominated flame retardant 1: Brominated epoxy, F-2100, ICL, Israel;

[0035] Brominated flame retardant 2: brominated polystyrene, SAYTEX 621, Albemarle, USA;

[0036] Flame retardant synergist: sodium antimonate, SA-F, Chenzhou Antimony Industry;

[0037] Halogen absorbent 1: zeolite, average particle size 8 μm, Shandong Xurui;

[0038] Halogen absorbent 2: hydrotalcite, DHT-4A, average particle size 0.5 μm, Kyowa Chemical, Japan;

[0039] Halogen absorbent 3: zeolite, average particle size 50 μm, Shandong Xurui;

[0040] Halogen absorbent 4: activated alumina, average particle size 5 μm, Chengdu Hengyi Chemical;

[0041] Talc 1: average particle size 0.65 μm, HTP Ultra 5L, Liaoning Aihai Yimi Mining;

[0042] Talc 2: average particle size 4.7 μm, TYT-999, Guangzhou Tianyuan Chemical;

[0043] Talc 3: average particle size 8.0 μm, AH-1250N6, Guangxi Longsheng Huamei Talc;

[0044] Talc 4: average particle size 0.5 μm, source powder;

[0045] Toughening agent: ethylene-acrylate-glycidyl methacrylate terpolymer, commercially available;

[0046] Glass fiber: glass fiber diameter 10μm, ECS10-4.5-T436H, Taishan Glass Fiber Co., Ltd.;

[0047] Antioxidant: Commercially available,

[0048] Lubricant: Commercially available;

[0049] The toughening agent, glass fiber, antioxidant and lubricant used in the parallel experiments of the embodiments and comparative examples are consistent.

[0050] Examples 1-11 and Comparative Examples 1-11

[0051] The component contents (parts by weight) of Examples 1-11 of the present invention and Comparative Examples 1-11 are shown in Tables 1 and 2;

[0052] Table 1

[0053]

[0054] Table 2

[0055]

[0056]

[0057] The preparation methods of Examples 1-11 and Comparative Examples 1-11 are:

[0058] The dried raw materials are weighed and added into a mixer for uniform mixing, and then fed into a twin-screw extruder. The feed rate of the twin-screw extruder is adjusted to 600 kg / hour. The polyester composite material is obtained by extrusion, drawing, cooling, pelletizing and drying. The drying process of the PBT resin is as follows: the PBT resin is dried at 130°C for 5 hours. The parameters of the twin-screw extruder are as follows: the temperatures of each section of the screw from the feed port to the die are 230°C, 240°C, 240°C, 250°C, 260°C, 250°C, 240°C, 230°C and 220°C respectively; and the screw speed is 400rpm.

[0059] Effect example

[0060] The effect examples of the present invention verify the performance of the products prepared in Examples 1-11 and Comparative Examples 1-11; the products obtained by extrusion and pelletization are dried at 120-130°C for 3-4 hours; wherein the tensile strength is tested according to ISO 527-2012 standard, and the flame retardant specimens are tested according to UL94-2013 standard; the heat resistance evaluation method is to prepare the national standard tensile specimens for testing by injection molding according to ISO 527-2012 standard, place the specimens in a high temperature oven at 190°C for aging, and test the mechanical properties after aging for 1000 hours; the yellowing resistance evaluation method is to inject a standard color plate, use a colorimeter to test the initial Lab value, then place the color plate in a high temperature oven at 180°C for aging for 168 hours, take out the color plate, test the Lab value after aging, and the ΔE before and after aging is the yellowing index. The larger the ΔE, the more obvious the yellowing. The results are shown in Table 3;

[0061] Table 3

[0062]

[0063]

[0064] It can be seen from Table 3 that when the technical solution of the present invention is adopted, the obtained products have excellent heat resistance in addition to flame retardancy. The flame retardancy grade of the obtained products is V-0, and the tensile property retention rate after aging in a high temperature oven at 190°C for 1000h is above 67%; and the products also have excellent yellowing resistance, wherein the yellowing resistance value is below 14△E;

[0065] It can be seen from Examples 1-4 and Comparative Examples 1-2 that the mass ratio of the halogen absorber to the talc powder has a significant effect on the heat resistance of the product. When the mass ratio of the halogen absorber to the talc powder is in the range of 1:(1-5), the tensile strength retention rate is above 67%, and the yellowing resistance value is below 13ΔE; especially when the mass ratio of the halogen absorber to the talc powder is in the range of 1:(2-3), the comprehensive performance of the obtained product is more excellent, specifically, the tensile performance retention rate is above 72%, and it has long-term heat resistance;

[0066] It can be seen from Example 1 and Comparative Examples 3-4 that when the mass ratio of the halogen absorber and the talcum powder is within the range but the number of added portions of the halogen absorber or the talcum powder is not within the scope of the present invention, the tensile property retention rate of the obtained product after aging for 1000 hours in a 190°C high-temperature oven decreases, and the tensile property retention rate decreases by 16.22-25.68% compared with that in Example 1; and the yellowing resistance of the product also decreases significantly, and the yellowing resistance values ​​in Comparative Examples 3-4 increase by 69.23-92.31% compared with the yellowing resistance values ​​in Example 1;

[0067] It can be seen from Example 1, Example 10, Comparative Example 5 and Comparative Example 11 that the average particle size of talc powder will also have a significant impact on the heat resistance of the product. When the average particle size of talc powder is within the range of the present invention, the tensile property retention rate of the obtained product after the thermal oxygen aging test is above 72%. If the average particle size of talc powder is not within the range of the present invention, the heat resistance and yellowing resistance of the obtained product are significantly reduced.

[0068] It can be seen from Example 1 and Examples 8-9 that when the average particle size range of the halogen absorber is further preferably 0.1-10 μm, the heat resistance of the obtained product is more excellent; it can be seen from Example 1 and Comparative Example 10 that when the selected halogen absorber is not the type of the present invention, the heat resistance and yellowing resistance of the obtained product are significantly reduced;

[0069] It can be seen from Example 1 and Comparative Examples 6-9 that when either the halogen absorber or talcum powder is reduced, the heat resistance of the obtained product is significantly reduced;

[0070] It can be seen from Examples 1 and 11 that the intrinsic viscosity of the PBT resin will also affect the heat resistance and yellowing resistance of the product.

[0071] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A PBT composite material, characterized in that: The PBT composite material comprises the following components in parts by mass: 40-60 parts of PBT resin, 25-40 parts of glass fiber, 8-20 parts of brominated flame retardant, 1-5 parts of flame retardant synergist, 0.3-1.1 parts of halogen absorbent, and 0.5-2 parts of talc; The average particle size of the talc powder is 0.6-5 μm; The mass ratio of the halogen absorbent to talcum powder is 1:(1-5); The halogen absorbing agent is hydrotalcite or zeolite; The average particle size of the halogen absorbent is 0.1-10 μm or 50 μm.

2. The PBT composite material according to claim 1, characterized in that: The mass ratio of the halogen absorbent to talcum powder is 1:(2-3).

3. The PBT composite material according to claim 1, characterized in that: The brominated flame retardant is at least one of brominated epoxy, brominated polystyrene, brominated polycarbonate, decabromodiphenylethane, pentabromobenzyl polyacrylate, and bromotriazine.

4. The PBT composite material according to claim 1, characterized in that: The flame retardant synergist is an antimony-containing flame retardant.

5. The PBT composite material according to claim 1, characterized in that: The PBT composite material further comprises the following components in parts by weight: 0.01-5 parts of a toughening agent and 0.01-1 parts of a processing aid.

6. The PBT composite material according to claim 5, characterized in that: At least one of the following (a)-(d): (a) the intrinsic viscosity of the PBT resin is 0.7-1.3 dL / g at 25°C; (b) the glass fiber is an alkali-free glass fiber treated with a coupling agent; (c) the toughening agent is at least one of ethylene-acrylate-glycidyl methacrylate terpolymer, ethylene-acrylate binary copolymer, ethylene-vinyl acetate, and glycidyl methacrylate grafted ethylene-octene copolymer; (d) The processing aid is at least one of a lubricant and an antioxidant.

7. The method for preparing the PBT composite material according to claim 6, characterized in that: The preparation method comprises the following steps: weighing the dried raw materials, mixing them and sending them into a twin-screw extruder, and performing extrusion, strip drawing, cooling, pelletizing and drying to obtain a PBT composite material.

8. The preparation method according to claim 7, characterized in that: The parameters of the twin-screw extruder are: feeding speed is 450-800kg / hour; the temperature of each section of the screw from the feeding port to the head is 220-230℃, 230-240℃, 230-240℃, 240-250℃, 250-260℃, 240-250℃, 240-250℃, 230-240℃, 220-230℃ respectively; the screw speed is 250-400rpm.

9. Application of the PBT composite material according to any one of claims 1 to 6 in the field of household appliances and electronic appliances.

Citation Information

Patent Citations

  • High-CTI halogen-containing flame-retardant reinforced PBT composite material as well as preparation method and application thereof

    CN112745640A

  • Low-TVOC flame-retardant reinforced PBT composite material and preparation method and application thereof

    CN112745641A